Analgesic effect of coconut shell (Cocos nucifera L) liquid smoke on mice - Meircurius Dwi C.S; Tantiana Tantiana; Ira Arundina (Dental Journal (Majalah Kedokteran Gigi), 2012)
Background: Drugs can be used to eliminate pain by inhibiting the activity of conversing arachidonic acid into prostaglandin. The chemical compositions of coconut shell are cellulose, pentosan, lignin, solvent extraction, uronat anhydrous, nitrogen, and water. One active ingredient in coconut shell is phenyl propanoid (consisting in lignin structure) and guaicol. Phenyl propanoid and guaicol are phenolic compounds that can be used as antioxidant, antiseptic, anti-inflammatory, anesthetic and analgesic. Liquid smoke of coconut shell (Cocos nucifera L) contains phenolic compound is believed able to bind a component conversing arachidonic acid into prostaglandin. Purpose: The study was aimed to examine the analgesic effect of liquid smoke of coconut shell (Cocos nucifera L). Methods: The study was a laboratory experimental research, conducted on 2-3 months old male mice (Mus musculus) with 20-30 grams of weight. There were control group and treatment groups each of which had seven mice. Control group was orally given 0.01 ml/weight (ml/gr) of distilled water, after 30 minutes 0.01 ml/weight (ml/gr) of acetic acid 0.6% was delivered via intraperitoneal injection. The treatment groups were given liquid smoke of coconut shell (Cocos nucifera L) with the concentrations of 25%, 50%, and 100% respectively. The analgesic effect was then determined by decreasing of writhing reflex on mice recorded every 5 minutes for 30 minutes. Results: There were significant differences of writhing reflexes in the treatment groups given liquid smoke of coconut shell with the concentrations of 25%, 50%, and 100%. The higher concentration of liquid smoke the higher its analgesic effect. Conclusion: Liquid smoke of coconut shell (Cocos nucifera L) has analgesic effect.Latar belakang: Salah satu mekanisme obat yang digunakan untuk menghilangkan rasa nyeri adalah menghambat aktivitas konversi asam arakhidonat menjadi prostaglandin. Komposisi kimia tempurung kelapa terdiri dari selulosa, petosan, lignin, solvent, uronat unhidrat, nitrogen dan air. Salah satu bahan aktif dalam tempurung kelapa adalah phenyl propanoid (terdapat dalam struktur lignin) dan guaiakol. Phenyl propanoid dan guaiakol adalah suatu senyawa fenol yang mempunyai sifat sebagai antioksidan, antiseptic, anti-inflamasi, anastesi dan analgesik. Liquid smoke tempurung kelapa (Cocos nucifera L)mengandung senyawa fenol yang dapat mengikat komponen dalam konversi asam arakhidonat menjadi prostaglandin. Tujuan: Studi ini bertujuan untuk meneliti efek analgesik dari liquid smoke tempurung kelapa (Cocos nucifera L). Metode: Penelitian ini adalah eksperimental laboratoris dengan jenis post test only control group design pada mencit (Mus musculus) jantan usia 2-3 bulan dengan berat badan 20-30gram. Kelompok kontrol dan perlakuan terdiri dari 7 hewan coba. Kelompok kontrol diberi aquades 0.01ml/bb (ml/gr) (po) dan setelah 30 menit diberi asam asetat 0.6% 0.01ml/bb (ml/gr) (ip). Kelompok perlakuan diberi liquid smoke tempurung kelapa (Cocos nucifera L) dengan konsentrasi 25%, 50% and 100%. Efek analgesik ditentukan dengan melihat penurunan writhing reflex (liukan atau geliat tubuh hewan coba) yang dihitung setiap 5 menit selama 30 menit. Hasil: Terdapat perbedaan yang bermakna jumlah writhing reflex pada pemberian liquid smoke tempurung kelapa konsentrasi 25%, 50% dan 100%. Semakin tinggi konsentrasi liquid smoke, semakin tinggi pula efek analgesic yang ditimbulkan. Kesimpulan: Liquid smoke tempurung kelapa mempunyai efek analgesik.